1994
DOI: 10.1002/mpo.2950220202
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children with leukemia

Abstract: Children with cancer represent a high-risk group for protein-energy malnutrition due to side effects associated with treatment. Assessment of nutritional status at the time of diagnosis and during treatment is, therefore, essential for planning nutritional intervention. We studied the nutritional status of 25 children with leukemia [9 newly diagnosed/relapsed (D/R) leukemic patients and 16 children with leukemia in remission (REM)]. Plasma proteins (prealbumin, PA; albumin, Alb; transferrin, Tr; retinol-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…In this Indian study show that there is 13 (52%) patients out of these 25 newly diagnosed ALL were underweight at presentation, twelve patients (48%) were wasted. Nine (36%) of them were malnourished according to MUAC [16]. Our study is comparable Rajesh et al study [17].…”
Section: Archives In Cancer Researchsupporting
confidence: 86%
See 3 more Smart Citations
“…In this Indian study show that there is 13 (52%) patients out of these 25 newly diagnosed ALL were underweight at presentation, twelve patients (48%) were wasted. Nine (36%) of them were malnourished according to MUAC [16]. Our study is comparable Rajesh et al study [17].…”
Section: Archives In Cancer Researchsupporting
confidence: 86%
“…et al was carried out on study group comprised 25 children with newly diagnosed ALL, their age range from (1-12) year, eighteen of them are male and seven are females [16]. In this Indian study show that there is 13 (52%) patients out of these 25 newly diagnosed ALL were underweight at presentation, twelve patients (48%) were wasted.…”
Section: Archives In Cancer Researchmentioning
confidence: 81%
See 2 more Smart Citations
“…Kibirige et al [10] reported that median weight:height ratio and serum albumin concentrations may be useful measurements in children newly diagnosed with leukemia to indicate which patients will require supplementary nutrition. Yu et al [15] also reported that low plasma protein concentrations can be ascribed to mild malnutrition in children with newly diagnosed or relapsed leukemia. Merritt et al [16] reported similar results in pediatric cancer patients, suggesting that abnormal serum albumin is a more common indicator of acute metabolic response to fever and infection than decreased body mass.…”
Section: Discussionmentioning
confidence: 99%